Adoption and Resistance to Innovation: A Case of Mobile Payment Services - Lai, Ming-Cheng; Lee, Tzu-Ying; Yang, Yann-Jy (Xing Xiao Ping Lun, 2018)
Under the rapid development of science and technology, human life forms are rapidly evolving. Mobile payment is gradually favored by consumers under the trend of mobile devices and mobile networks. However, how consumers adopt new products or services is highly relevant to their personal traits, and it also has a positive and negative impact on the intentions of innovation. Therefore, this study focuses on the relationship between consumer innovativeness, gadget loving, and their influence on consumer adoption of mobile payment services. There are many reasons will influence the adoption of new products or services. In addition to the positive personality traits, there also many negative factors. For negative factors, this paper focuses on how innovation resistance influences the adoption of mobile services. In this study, there has a total of 551 valid questionnaires, and the hypothesis test of structural model was using PLS 2.0.The results show that (1) global innovativeness has significant positive influen